PENGARUH PENERAPAN APLIKASI e-GOVERNMENT PEMBAYARAN PAJAK KENDARAAN BERMOTOR TERHADAP KINERJA CASH ADMINSTRATION (Studi Kasus di Kantor Unit Pelaksana Teknis Dinas Pendapatan Provinsi Jawa Timur Trenggalek) - Purwokoadi, Sungging (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
This study entitled "The Effect Of E-Government Applications Vehicle TaxPayments On The Performance Of Cash Administration". Revolutionarytechnology telecommunications, media and information technology (ICT)affects the increasing demands and expectations of the public on fast publicservice, accurate, and inexpensive but excellent. Democratization, impacting theincreasing demands people's participation in public policy, demandtransparency, accountability and quality of public performance. Descriptiveresearch is a study of the problems in the form of the current facts of apopulation which aims to test hypotheses or answer questions relating to thecurrent state of the subject under study. Correlational research is to study thecharacteristics of the problem in the form of a correlational relationship betweentwo or more variables which aims to determine whether there is an associationbetween two or more variables, as well as how far the correlation that existsbetween the variables studied. The research method of data with secondary dataresearch types are the type of research data obtained institutional data from theUnit Pelaksana Teknis Dinas Pendapatan Provinsi Jawa Timur throughobservation, also use this type of research primary data obtained through fieldsurveys. The research sample used all employees serve as responden. Thecollecting data through observation and questionnaire. Answer the problemformulation used descriptive statistical analysis tool with the help of a frequencytable and regression models using SPSS release 16. Hypothesis testing produces,indicating that the hypothesis 1 is accepted, it means the variable partialapplication of e-Banking System has a positive and significant impact on theperformance of Cash Adminstration. The results of hypothesis testing indicatesthat the hypothesis 2 in this study received, meaning that in partial RevenueApplication Implementation (SAP) has a positive and significant impact on theperformance of Cash Adminstration Variation of performance can be explainedby the Adminstration Cash independent variables of e-Banking SystemImplementation and Application of Revenue Application (SAP) and while the explained by other factors. The Performance of Cash Administration will riseproperly Implementation of e-Banking System and Application SystemApplication Revenues(SAP) is well managed.